Efektivitas Pembelajaran Online Menggunakan Media Zoom Cloud Meeting Terhadap Hasil Belajar Siswa Kelas V SD Negeri 37 Pekanbaru Pada Masa Covid-19 - Elsunarti Nurel; Nursalim Nursalim; Muhammad Saifuddin; Anggi Fitri; Yundri Akhyar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This study aims to determine the effectiveness of online learning using media zoom cloud meetings on student learning outcomes. With a quantitative method approach and pre-experimental research design. The pre-experimental form used was the one-group pretest-posttest design. The use of pretest and posttest is expected to be more accurate during the study because it can compare with the situation before being treated. To obtain correct and accurate data, questionnaires and test questions were used as data collection tools. The data were tested using a two-way ANOVA with the help of the SPSS-23 application. The results showed that online learning using zoom cloud meeting media was effective in student learning outcomes during the Covid-19 pandemic.